2017
DOI: 10.1158/2159-8290.cd-16-1045
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Landscape of Inherited Polymorphisms with Somatic Events in Cancer

Abstract: Recent studies have characterized the extensive somatic alterations that arise during cancer. However, the somatic evolution of a tumor may be significantly affected by inherited polymorphisms carried in the germline. Here, we analyze genomic data for 5954 tumors to reveal and systematically validate 412 genetic interactions between germline polymorphisms and major somatic events, including tumor formation in specific tissues and alteration of specific cancer genes. Among germline-somatic interactions, we find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 78 publications
6
127
0
Order By: Relevance
“…Our genetic background, however, affects how and where tumours develop, which could improve screening and pre-emptive preventive designs. 6 …”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our genetic background, however, affects how and where tumours develop, which could improve screening and pre-emptive preventive designs. 6 …”
Section: Preventionmentioning
confidence: 99%
“…50 Germline variants and somatic events are also intricately linked, with specific haplotypes of JAK2 Val617Phe in myeloproliferative neoplasms 51 and EGFR exon 19 microdeletions and Thr790 mutations in non-small-cell lung cancer (NSCLC). 52 In a pan-cancer study 6 (22 tumour types, about 6000 tumours) integrating common germline loci with somatic changes, inherited variation was found to affect somatic evolution of neoplasia by directing where (organ site) and how (which genes are affected transcriptionally) cancer develops, highlighting the remarkable prospect of anticipating and intercepting key early events during tumour development. Multigene testing is broadening the spectrum of cancer risk linked to various hereditary syndromes, frequently identifying individuals with high-penetrance germline mutations that are unexpected from clinical history (eg, colorectal cancer in patients with BRCA1 or BRCA2 mutations).…”
Section: Preventionmentioning
confidence: 99%
“…Using matched germline and tumor genomic data for nearly 6000 patients, it was possible to systematically screen for and validate 412 associations between germline loci and tumor site as well as for a subset of common tumor genotypes involving known cancer genes. 8 By this approach, we sought to identify inherited factors that could influence where a tumor will emerge and what cancer genes might be involved in the tumor's development ( Fig. 1).…”
mentioning
confidence: 99%
“…As a previous study reported, genetic background could influence the somatic evolution of a tumor by modifying the likelihood of acquiring mutations in specific cancer genes,37 which could possibly explain why there were a number of SNP‐gene pairs found in our study.…”
Section: Discussionmentioning
confidence: 72%